Economics of shifting land from field crops to hog plum (Spondias mombin L.) cultivation in southern Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2021)
The study was carried out to analyse the economics of shifting land from field crops to hog plum cultivation in southern Bangladesh during July to September 2018. A total of 120 farmers were selected by using multistage stratified random sampling technique to collect primary data. Result of the study shows that the per hectare average total cost of hog plum cultivation was Tk. 94,126. The average yield of hog plum was 7.97 t ha-1. Net return from hog plum cultivation was Tk. 126,921 per hectare. By cultivating hog plum, farmers obtained 56 to 93% higher net return than the other existing cropping patterns. Since the BCR (2.94), NPV (Tk. 2215,000) and IRR (59%) were very high, the land shifting decision towards hog plum cultivation was sensible. However, BCR was very low in the initial stages of hog plum plantation. Initial investment support from public or private sector could facilitate the growth of this cultivation practice.Int. J. Agril. Res. Innov. Tech. 10(2): 155-163, December 2020